(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Continuous education and training play a pivotal role in advancing healthcare quality by ensuring that lab technicians and nurses remain equipped with the latest knowledge, skills, and best practices. This article explores the importance of ongoing education for both professions, highlighting its impact on patient care, diagnostic accuracy, and interdisciplinary collaboration. Through a review of current practices and emerging trends, it delves into the various methods and resources available for continuous learning, emphasizing the need for a collaborative approach between healthcare institutions, educational providers, and professional associations. Case studies and examples illustrate the tangible benefits of investing in the professional development of lab techs and nurses, ultimately contributing to improved healthcare outcomes and enhanced patient safety.